“I Stand Out Like a Raven”: Depicting the Female Detective and Tudor History in Nancy Bilyeau’s The Crown - Beyer Charlotte (American, British and Canadian Studies Journal, 2017)
This article examines the portrayal of female identity and crime in the Tudor period in Nancy Bilyeau’s contemporary historical crime fiction novel, The Crown (2012). Featuring a female detective figure, Joanna Stafford, Bilyeau’s novel forms part of the wealth of contemporary fiction using Tudor history as context, reflecting a continued interest in and fascination with this period and its prominent figures. This article examines Bilyeau’s representation of the Tudor period in The Crown through the depiction of English society and culture from a contemporary perspective, employing genre fiction in order to highlight issues of criminality. My investigation of The Crown as crime fiction specifically involves analysing gender-political questions and their portrayal within the novel and its tumultuous historical context. This investigation furthermore explores the depiction of agency, individuality, religion, and politics. The article concludes that Bilyeau’s suspense-filled novel provides an imaginative representation of Tudor history through the prism of the crime fiction genre. Central to this project is its employment of a resourceful and complex female detective figure at the heart of the narrative.